Financial literacy and financial behavior: Do women lag behind? - Lukas Menkhoff; Antonia Grohmann; Olaf Hübler; Roy Kouwenberg (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This research challenges the stylized fact of a gender gap in financial literacy, i.e. the finding that women lag behind men in this respect. Our data which samples middle-class people from Bangkok does not show a gender gap, neither in regards to financial literacy nor regarding various kinds of informed financial decision making. This result is not explained by men s low financial literacy. It may be partially explained by high income of our target group and it seems likely to be influenced by Thailand s cultural background, such as the low degree of masculinity.
Keywords: D14; J16; O16; 330